PRINSIP-PRINSIP KEPEMIMPINAN DALAM HADIS NABI DAN RELEVANSINYA BAGI PEMERINTAHAN MODERN - Muhammad Izhar; Salsabila Azahra (DIRAYAH : Jurnal Ilmu Hadis, 2026)
This article examines the principles of leadership in the hadiths of the Prophet Muhammad (peace be upon him) and their relevance to modern governance. The study focuses on the hadith prohibiting the seeking of leadership positions as recorded in Sahih al-Bukhari and Sunan al-Tirmidhi, as well as the hadith concerning the entrustment of authority to those who are unqualified. Using a library research approach with thematic (mawḍūʿī) analysis, this article explores the normative and contextual meanings of these hadiths. The findings indicate that these traditions contain fundamental principles of Islamic leadership, including: leadership as a divine trust (amānah), the necessity of competence and eligibility (ahliyyah), moral integrity (ṣidq and ʿadālah), rejection of ambition for power, belief in divine assistance for sincere leaders, prioritization of public welfare (maṣlaḥah) over rigid formalism, and accountability (masʾūliyyah). In the hadith perspective, leadership is not a privilege to be pursued, but a heavy trust for which one will be held accountable before both God and society. In the context of modern governance, these principles remain highly relevant, particularly in addressing public trust crises, nepotism, abuse of authority, and weak integrity among public officials.